Digital transformation of traditional restaurant micro, small, and medium enterprises (MSMEs) in Sri Lanka: University - community development participatory action research - Liyanage, H.L.M.K.; Kanchana, H.P.G.; Prabhashana, I.G.T.S.; Fernando, J.T.S.; Pirashanthiny, K.; Dulanjana, K.M.T.N.; Dasanayaka, K.M.C.S.; Madhusanka, K.M.P.R.; Jayathilaka, K.A.S.P.; Jayalath, K.A.U.D.; Dilogini, S. (Rajarata University of Sri Lanka, 2024)
This Participatory Action Research investigates the digital transformation of Fluffy Ice Bar, a startup restaurant in Jaffna, Sri Lanka, which primarily relies on word-of-mouth marketing and lacks social media presence. The objective was to establish and manage social media platforms, including Facebook, lnstagram, TikTok, and WhatsApp, to enhance brand visibility, customer engagement, and market differentiation. By creating a unique digital identity, researchers aim to attract more customers and improve the market positioning. The study employs PAR, involving marketing students from the University of Jaffna, chosen because it allows direct interaction with the subject matter, making the research realistic and applicable to solving real-life problems faced by MSMEs as part of university community development. Data were collected through interviews with restaurant owners, employees, and customers to identify the challenges in adopting digital marketing strategies. Key obstacles include the absence of online payment features, a lack of digital marketing proficiency, and the need for an online menu system that hinders restaurants' reach and growth. These findings underscore the owner's limited technical knowledge as a significant barrier to business expansion. To address these challenges, a structured digital marketing approach was developed, comprising content creation, marketing strategies, targeted ad campaigns, and online payment solutions (e.g., Lanka Pay). We introduced an online menu system accessible via QR codes to streamline the customer experience and enhance operational efficiency. Additionally, social media analytics was employed to further optimize efforts. Efforts have focused on building brand recognition by engaging content and influencer collaborations on platforms such as TikTok and Instagram, aimed at driving customer acquisition and sales growth. Practical implications include establishing a distinctive Facebook page, leveraging content marketing, integrating traditional marketing methods such as posters, and incorporating a QR code-based online menu system to build customer trust and engagement. These strategies collectively aim to optimize marketing efforts, maximize reach, and improve customer satisfaction, supporting Fluffy Ice Bar's digital transformation and growth objectives.
Keywords: Digital transformation; Marketing challenges; Participatory action research; Restaurant micro, small, and medium enterprises; Sri Lanka